O idoso e a internet : um estudo com participantes do grupo “UnAPI na quarentena” - Dias, Luana Curitiba (2022)
Supported by the Theory of Social Representations, this work aimed to know and analyze the Social Representation of the internet and of being elderly for elderly participants of the WhatsApp group “UnAPI in quarantine”, an interaction tool that was necessary due to the pandemic caused by the new Coronavirus. To achieve the proposed objectives, two instruments were used: at first, the application of an online questionnaire with the help of Google Forms using the OpenEvoc Software for analysis of the free evocation of words, which had the participation of 79 elderly, 77 women and 2 men; in a second moment, online interview, through video calls or call, with 08 elderly women using the content analysis technique to analyze these interviews. The representation of being elderly permeated the recognition of old age as a moment that has not yet arrived, or with a strong link with the health/disease issue, despite the recognition of the possibility of having more experience and wisdom; the internet, inserted in the daily lives of these elderly people, was represented through its functionality of informing, allowing interaction, communication and fun; and UnAPI was perceived as a space for learning, knowledge and, above all, welcoming. It is hoped that this study will contribute to the view of old age as a diverse process, possible to be lived in a healthy and happy way, but which also needs attention from public agents aiming at greater education and training to live this phase that is also irreversible and universal